WO3 passivation layer-coated nanostructured TiO2: An efficient defect engineered photoelectrode for dye sensitized solar cell. (May 2021) - Babu, Arya; Vasanth, Arya; Nair, Shantikumar; Shanmugam, Mariyappan
Abstract: Major loss factors for photo-generated electrons due to the presence of surface defects in titanium dioxide (TiO2 ) were controlled by RF-sputtered tungsten trioxide (WO3 ) passivation. X-ray photoelectron spectroscopy assured the coating of WO3 on the TiO2 nanoparticle layer by showing Ti 2p, W 4f and O 1s characteristic peaks and were further confirmed by X-ray diffraction studies. The coating of WO3 on the TiO2 nanoparticle layer did not affect dye adsorption significantly. Dye sensitized solar cells (DSSCs) fabricated using WO3 -coated TiO2 showed an enhancement of 10% compared to DSSCs fabricated using pristine TiO2 -based photo-electrodes. It is attributed to the WO3 passivation on TiO2 that creates an energy barrier which favored photo-electron injection by tunneling but blocked reverse electron recombination pathways towards holes available in highest occupied molecular orbital of the dye molecules. It was further evidenced that there is an optimum thickness (duration of coating) of WO3 to improve the DSSC performance and longer duration of WO3 suppressed photo-electron injection from dye to TiO2 as inferred from the detrimental effect in short circuit current density values. RF-sputtering yields pinhole-free, highly uniform and conformal coating of WO3 onto any area of interest, which can be considered for an effective surface passivation for nanostructured photovoltaic devices.